A nested-PCR assay for detection of Xylella fastidiosa in citrus plants and sharpshooter leafhoppers - Ciapina, L. P.; Alves, LMC; Lemos, EGM (Blackwell Publishing, 2004)
Aims: Detection of Xylella fastidiosa in citrus plants and insect vectors.Methods and Results: Chelex 100 resin matrix was successfully standardized allowing a fast DNA extraction of X. fastidiosa. An amplicon of 500 bp was observed in samples of citrus leaf and citrus xylem extract, with and without symptoms of citrus variegated chlorosis, using PCR with a specific primer set indicating the presence of X. fastidiosa. The addition of insoluble acid-washed polyvinylpyrrolidone (PVPP) prior to DNA extraction of insect samples using Chelex 100 resin together with nested-PCR permitted the detection of X. fastidiosa within sharpshooter heads with great sensitivity. It was possible to detect up to two bacteria per reaction. From 250 sharpshooter samples comprising four species (Dilobopterus costalimai, Oncometopia facialis, Bucephalogonia xanthopis and Acrogonia sp.), 87 individuals showed positive results for X. fastidiosa in a nested-PCR assay.Conclusions: the use of Chelex 100 resin allowed a fast and efficient DNA extraction to be used in the detection of X. fastidiosa in citrus plants and insect vectors by PCR and nested-PCR assays, respectively.Significance and Impact of the study: the employment of efficient and sensitive methods to detect X. fastidiosa in citrus plants and insect vectors will greatly assist epidemiological studies.
Keywords: Chelex 100; citrus variegated chlorosis; DNA extraction; Nested PCR; sharpshooter; Xylella fastidiosa